The The Existence of Sharia Financial Institutions in The Muslim Minority in Yala Province, Thailand: english - sinurat, Nuriyani Devi; Rahmayati (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam Syarifuddin Lumajang, 2023)
The sharia financial system is a system that adheres to the Al-Quran and Hadith. Statistical data show that Southeast Asia has become one of the centers for the development of the global Islamic finance industry including Indonesia, Malaysia, Brunei Darussalam, Singapore, Thailand and the Philippines. Therefore the purpose of this study is to find out in depth about the existence of Islamic financial institutions in the Yala province of Thailand. Utilizing a qualitative approach, or research to identify aspects or characteristics of social impacts that cannot be measured, explained, or defined using a qualitative approach, is the strategy used, with data collection techniques using observation and questionnaire techniques. The conclusion is that there is an influence of the Muslim minority on the development of Islamic financial institutions in the Yala province of Thailand, even though people are starting to become aware of using Islamic financial institutions in banking transactions.